2011
DOI: 10.1038/jp.2011.170
|View full text |Cite
|
Sign up to set email alerts
|

Predischarge non-invasive risk assessment for prediction of significant hyperbilirubinemia in term and late preterm neonates

Abstract: Objective: To evaluate efficacy of predischarge transcutaneous bilirubin (TcB) measurement and clinical risk assessment in predicting hyperbilirubinemia needing treatment.Study Design: A diagnostic test was performed in a prospective cohort study conducted at a teaching hospital in North India. Subjects included healthy neonates with a gestation period of X35 weeks or birth weight X2000 g. Maternal, neonatal and delivery risk factors for hyperbilirubinemia were prospectively collected. TcB was measured in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…There were wide variations in the primary outcomes, diagnostic criteria and putative risk factors explored across studies. In the three prospective cohort studies [ 25 , 30 , 31 ] included in the meta-analysis, follow-up was within 7 postnatal days and the reported attrition rate was less than the 20% general rule of thumb [Song & Chung, 2010].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were wide variations in the primary outcomes, diagnostic criteria and putative risk factors explored across studies. In the three prospective cohort studies [ 25 , 30 , 31 ] included in the meta-analysis, follow-up was within 7 postnatal days and the reported attrition rate was less than the 20% general rule of thumb [Song & Chung, 2010].…”
Section: Resultsmentioning
confidence: 99%
“…The pooled data of the two studies from India [ 24 , 33 ] that explored the contribution of UGT1A1 polymorphisms to the risk of neonatal hyperbilirubinemia showed significant cumulative risk estimate (OR, 4.92; 95% CI, 1.30–18.62, p = 0.019), with high heterogeneity (I 2 = 74.0%). Gestational age in relation to the risk of severe hyperbilirubinemia in two studies from India [ 30 , 31 ] and the pooled data showed that infants with low gestational age (<37 weeks) were at increased risk of severe hyperbilirubinemia (OR, 1.71; 95% CI, 1.40–2.11, p<0.0001), with low heterogeneity (I 2 = 0.0%). Four studies from Nigeria [ 26 , 27 ], Egypt [ 28 ] and India [ 33 ] examined the role of infant weight on admission for severe jaundice.…”
Section: Resultsmentioning
confidence: 99%
“…Transcutaneous bilirubinometers correlate well with serum bilirubin and to be valid indicators of hyperbilirubinemia in preterm and term neonates (Kaur et al . ). There are also relatively inexpensive instruments such as the icterometer and the jaundice meter that are non‐invasive diagnostic tools that have been used for many years to improve the visual assessment of jaundice in neonates and could be used in community‐based studies in low‐resource settings.…”
Section: Discussionmentioning
confidence: 97%
“…There is need to assess neonatal jaundice objectively as clinical assessment through eye observation has limitation in picking at risk babies. 18,19 Early breastfeeding initiation still holds an upper hand in reducing incidence of neonatal jaundice in the first week of life.…”
Section: Resultsmentioning
confidence: 99%